Corporate Social Responsibility Audit: From Theory to Practice - Morimoto, Risako (Journal of business ethics, 2005)
This research examines the possibility of developing a new corporate social responsibility (CSR) auditing system based on the analysis of current CSR literature and interviews conducted with a number of interested and knowledgeable stakeholders. This work attempts to create a framework for social responsibility auditing compatible with an existing commercially successful environmental audit system. The project is unusual in that it tackles the complex issue of CSR auditing with a scientific approach using Grounded Theory. On the evidence discovered to date in the literature review and the interviews, CSR seems to be perceived by many as the social strand of sustainable development. However, there is far less agreement regarding its measurement. Both the literature review and the interview analysis indicate that developing an applied CSR auditing procedure will be a challenging task. This is principally due to the lack of formal study of this complex subject, which, despite the widespread debate it has engendered, still lacks a single and broadly accepted definition. The concepts developed from the findings of this research, together with the key factors identified in a literature review of CSR, were developed into a prospective CSR audit protocol.